PSYCHOSOMATIC FACTORS IN CARDIOLOGICAL, NEUROLOGICAL, AND JOINT DISEASES: INTEGRATION OF MENTAL AND PHYSICAL HEALTH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This paper provides an in-depth exploration of the link between cardiovascular, central nervous system, and joint disorders and their psychological influences. It investigates the areas of cardiology, neurology, and rheumatology from a psychosomatic perspective, underscoring the significant role of stress, depression, anxiety, and emotional strain in the development and progression of these conditions. The article also examines the body's physiological responses to psychological states, such as increased heart rate, headaches, and joint inflammation, illustrating their close relationship with mental health. Furthermore, it highlights the critical role of integrating psychotherapy, stress management strategies, and emotional well-being restoration as part of a holistic treatment approach for these diseases. The results indicate that effective treatment can be achieved not only through pharmacological interventions but also by incorporating psychological approaches.